Hubungan Sains dan Agama (Rekonstruksi Citra Islam di Tengah Ortodoksi dan Perkembangan Sains Kontemporer) - Arifullah, Mohd. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
Islam is now facing some negative image projections from many parties especially if they view Islam from its historical dimension. This article highlights these projections and providing Moslems of how they should behave responding to these charges objectively through self-critic and science-critic. By doing these, we, Moslems, can put these projections infair proportion. These problems are processed employing realism metaphysic approach together with its 3 analytical models namely historical analysis, archeological analysis of thoughts, and deconstructive analysis. The writer uncovers that understanding religion should not merely be based on its textual bases but should also be integrated with many other approctches and dimensions for a holistic understanding of Islam.